The Exordium of Adébáyọ̀ Fálétí’s Poetry - Adedotun Ogundeji (Yoruba Studies Review)
The background of Adébáyọ̀ Fálétí (1921 – 2017) was steeped in the Ọyọ̀ ́ Yorùbá culture. He had a princely connection to the throne of Ọyọ̀ ́ having been born by Dúrówadé Àyìnkẹ, a granddaughter of Prince Adé ́ ṣọ̀kàn, Bàbá Ìdódẹ, Aláàfin Àtìbà’s son, to Àkànbí Fálétí. Àkànbí Fálétí was a royal oral artist in the palace of Aláàfin Ṣiyanbọ́lá Oníkẹẹ̀ pé Ládìgbòlù (1911 – ́ 1944). He later practiced outside the palace, leading his own band, going about Ìlọrin and its environs and parts of Northern Yorùbáland. The late Pa David Adéníji of Ìwó, we reliably learnt, was one of his followers. Adébáyọ̀ Fálétí spent his early life in Ọyọ̀ ́ villages such as Àgbóóyè, Ọbanàǹkò and Kúrańgà (Ọlátúnji 1982a). Adébáyọ Fálétí learnt many Yorùbá tales and garnered other ̀ native wisdom from his father and other relations. Such relations include Jímọ̀ Ọládẹ̀jọ, who was adept in proverbs, and his childless aunt, an oríkì (charcterizational) poetry exponent. The western education he acquired and the Christianity he embraced were also part and parcel of his background. His primary school education was at Ọyọ̀ ́ (1939 – 1945), his secondary school education at Ìbàdàn Boys High school, Ìbàdàn, (1951 – 1955) and his University education at the University of Ìbàdàn (1965 – 1968). He took a bachelor’s degree in English with a subsidiary in French. There is no doubt that Adébáyọ̀ Fálétí would have been influenced by Yorùbá literary artists of his time, all of whom he studied in school. Among such Yorùbá literary precursors were A. K. Ajíṣafẹ, D. A. Ọbasá and D. ́ O. Fágúnwà. Adébáyọ Fálétí collected and transcribed oral poetic forms such ̀ as proverbs and oríkì following Obasá’s example before venturing into writing 110 Adedotun Ogundeji his own compositions. Though he had been writing before 1955, he did not come into the limelight until 1955, when his 719 lines long poem, “Ẹ̀dá Kò Láròpin” won the Festival of Arts award. This time may conveniently be considered the beginning of his poetic career. The poem also marked the direction which Adébáyọ̀ Fálétí’s important contributions to Yorùbá poetry was leaning. He adapted many traditional stories for his poetic compositions. There are 35 poems in the two collections of Adébáyọ̀ Fálétí’s Yorùbá poems (Ọlátúnjí 1984 b & 1984c), 13 in the first and 22 in the second. Adébáyọ̀ Fálétí’s poems, can conveniently be classified into two: the narrative and non-narrative. The narratives tell interesting stories, some of which are adapted from the Ifá corpus and other stories collected from his father, co-hunters and other sources. The non-narrative ones are made up of poetic discourses on various social and philosophical topics. There are eleven narrative poems in the two collections. The first contains ten, the second only one. It could therefore be safely concluded that the first is dedicated to narrative poems because only four of the thirteen poems in it are non-narrative. Since there is also only one narrative poem in the second, one could also assert that it is dedicated to non-narrative poems. Four of the eleven narrative poems, (‘Ẹ̀là Lọrọ̀ ’, ‘̀ Ṣàṣọrẹ’, ‘Alágbára Ilé àti Alágbára Oko’, and ‘Agbódóro ́ - gun’) are adapted from the Ifá corpus and there are strong evidences that ìjálá (Ogun poetry/hunter’s) is the original source of the story retold in ‘Adébímpé Ojẹ̀dòkun’. The poet was reported to have collected it from his father who informed him it was a true-life story (Ọlátúnjí 1982a). In our examination of the exordiums of Adébáyọ̀ Fálétí’s poems, we shall dwell more on his narrative poems than on his non-narrative poems and limit ourselves to the aforementioned two collections (Olatunji 1982b & 1982c).